Assessment of simulation modelling and real-time measurements for 3.15 and 17.28 kWp solar photovoltaic (PV) systems in Malaysia - Balasubramanian B.; Ariffin A.M.; Al-Zubaidi S.H. (International Journal of Renewable Energy Research, 2023)
Cells; Cytology; Equivalent circuits; Graphical user interfaces; Real time systems; Solar concentrators; Solar energy; Solar power generation; Solar radiation; Cell's temperatures; Graphic user interface; Photovoltaic systems; Portable simulation system; Simulation systems; Simulation-modelling; Solar irradiances; Solar photovoltaic rooftop system; Solar photovoltaics; UNITEN; Solar panels